Cultural Guardianship in Tourism: Indigenous Communities' Quest for Economic Stability and Identity Preservation - REDDY, Kiran; SAILESH, Bhaskar (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024DO - 10.14505/jemt.v15.2(74).08, 2024)
Purpose: This research aims to comprehensively analyze the impacts of tourism on indigenous communities, exploring economic, cultural, social, and environmental dimensions. It also seeks to understand indigenous perspectives on tourism development and identify future research directions for more sustainable approaches. Methodology: The review employs a systematic approach, conducting exhaustive searches across electronic databases and manual searches in relevant literature. Selection criteria prioritize studies focusing on economic, cultural, social, or environmental effects of tourism on indigenous communities. Thematic organization synthesizes key findings from the literature. Findings: The review highlights tourism's potential benefits for indigenous communities, such as income generation and cultural revitalization, alongside challenges like cultural appropriation and environmental degradation. Indigenous perspectives emphasize cultural preservation and equitable participation in tourism decision-making. Originality: This study's originality lies in its comprehensive analysis of indigenous tourism impacts, integrating diverse perspectives and guiding future research directions. By synthesizing existing research and amplifying indigenous voices, it contributes to understanding the complex interactions between tourism development, indigenous cultures, and sustainability.